# Solve for m 3(m+2)=2(m+3)+m 3(m+2)=2(m+3)+m
Since m is on the right side of the equation, switch the sides so it is on the left side of the equation.
2(m+3)+m=3(m+2)
Simplify 2(m+3)+m.
Simplify each term.
Apply the distributive property.
2m+2⋅3+m=3(m+2)
Multiply 2 by 3.
2m+6+m=3(m+2)
2m+6+m=3(m+2)
3m+6=3(m+2)
3m+6=3(m+2)
Simplify 3(m+2).
Apply the distributive property.
3m+6=3m+3⋅2
Multiply 3 by 2.
3m+6=3m+6
3m+6=3m+6
Move all terms containing m to the left side of the equation.
Subtract 3m from both sides of the equation.
3m+6-3m=6
Combine the opposite terms in 3m+6-3m.
Subtract 3m from 3m.
0+6=6
6=6
6=6
6=6
Since 6=6, the equation will always be true for any value of m.
All real numbers
The result can be shown in multiple forms.
All real numbers
Interval Notation:
(-∞,∞)
Solve for m 3(m+2)=2(m+3)+m

## Our Professionals ### Robert Kristofer ### Anna Frok ### Magnus Flores ### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top